Vitiligo: A Comprehensive Overview. Issue 1 (January 2021) - Stiegler, Julia; Brickley, Sylvana
Abstract : ABSTRACT: Vitiligo is a common condition. This article provides a comprehensive overview of vitiligo including the clinical presentation, associated comorbid conditions, treatment, emerging therapies, and psychosocial and cultural considerations.